Development and implementation of a strategic personnel management system according to goals based on key performance indicators - Karpenko, Andrii; Karpenko, Natalia; Shudrik, Oleksandr (Management and Entrepreneurship: Trends of Development, 2020)
In the conditions of competition and difficult economic situation, domestic thermal power companies face problems of ensuring their own efficient activity. This is significantly due to the low motivation of the company staff and its productivity. Therefore, an important direction for improving the performance of such businesses will be to create an effective system of direct material incentives for employees, especially with regard to optional bonuses or targeted bonuses based on the use of the KPI. The study is aimed at the development of a strategic personnel management system according to goals based on key performance indicators. The article proposes an approach to developing a Management by Objects (MBO) system based on absolute and relative numerical indicators of the Key Performance Indicators (KPI) performance of the organization as a whole and the decomposition of goals at the level of individual business processes and functional responsibilities of the units. Methodology: In the course of the research general, scientific, theoretical and empirical methods were used, among which are the following: analysis and generalization of literature on the research topic, methods of observation and comparison, structural methods, methods of coordination and formalization, graphical and tabular representation of data. The theoretical and practical database of the strategic personnel management system according to goals is considered as an information base of the research. The scientific significance of the work is that the issue of developing such a system for a municipal enterprise is covered, whose activity depends on the regulatory policy of the state. The role of key performance indicators of KPI is determined as an effective tool in the system of direct material incentives, which assesses the efficiency and effectiveness of business processes, actions and functions of management, specific production, technological and other activities. The reasons that makes it impossible to use KPI without a comprehensive program for improving the personnel management system are analyzed and identified. The practical significance of the results of the study is that a detailed step-by-step scheme for improving the personnel management system is proposed, which will enable the development and implementation of the KPI system to be developed. The use of KPI in the strategic personnel management system will allow the manager to better control the processes of operating activities, create real indicators of the implementation of the enterprise strategy and improve productivity. JEL Classification: А13, D20, L10, M12.